2011
DOI: 10.1007/s00432-010-0970-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the association studies of single nucleotide polymorphisms and hepatocellular carcinoma: a systematic review

Abstract: Two SNPs (rs1800562 of HFE and rs2279744 of MDM2) were associated with HCC with moderate epidemiological evidence and deserve further study and additional biological and clinical assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 66 publications
(81 reference statements)
1
50
1
Order By: Relevance
“…Alcoholic steatohepatitis (ASH) and nonalcoholic steatohepatitis (NASH)-associated cirrhosis also represent common etiological factors for HCC. In addition, host genetic variants, including single nucleotide polymorphisms (SNPs), have been showed to be associated with the development and progression of HCC (Jin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Alcoholic steatohepatitis (ASH) and nonalcoholic steatohepatitis (NASH)-associated cirrhosis also represent common etiological factors for HCC. In addition, host genetic variants, including single nucleotide polymorphisms (SNPs), have been showed to be associated with the development and progression of HCC (Jin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may be concluded that the GTSF1 gene may serve a role as a proliferation factor during various physiological processes, including growth, development, differentiation and reproduction in animals and plants. In terms of liver cancer, there have been numerous studies regarding the molecular markers associated with the development of liver cancer, and gene signatures with diagnostic and prognostic potential have been identified by the gene expression profiling of tumor tissues (15)(16)(17). In the present study, it was identified that GTSF1 mRNA expression in liver cancer tissue samples was increased compared with its expression in adjacent non-tumor liver tissues and healthy control liver tissues.…”
Section: Discussionmentioning
confidence: 50%
“…Some of the confirmed risk factors include exposure of aflatoxin B, chronic infection with hepatitis B virus or hepatitis C virus, excessive consumption of alcohol and tobacco, iron overload, and diabetes (Forner et al, 2012). In the last few years, numerous studies have pointed out that SNPs of certain cancer-related genes may be associated with the initiation and progression of HCC, either independently or in cooperation with identified risk factors (Jin et al, 2011;Nahon et al, 2012). The -765G>C (rs20417) and -1195G>A (rs689466) polymorphisms in the COX-2 gene are among the most extensively studied SNPs.…”
Section: Discussionmentioning
confidence: 99%